Pengaruh Pengalaman Wisatawan Dan Citra Destinasi Terhadap Minat Berkunjung Kembali Di Pantai Tanjung Bias - Sulhaini; Dwi Putra Buana Sakti (Khidmatuna (Jurnal Pengabdian Kepada Masyarakat), 2022)
This study aims to determine the effect of Tourist Experience and Destination Image on Revisit Interests. The type of research used in this research is associative research with a quantitative approach. The data collection method used is a survey sample using primary data collected directly from respondents using questionnaires. The population in this study were respondents aged over 17 years, and had made at least one visit, with a sample of 60 (sixty) respondents. Sampling using non-probability sampling with purposive sampling method, namely the determination of the sample with certain considerations. The data analysis tool used is Multiple Linear Regression using SPSS version 2.8. The results of data analysis show that: (1) Tourist experience has a positive and significant effect on revisit interest 0.032 < 0.05. (2) Destination image has a positive and significant effect on revisit interest 0.019 < 0.05.